A new species of Amphinemura (Plecoptera: Nemouridae) from the South of the Russian Far East - Teslenko, Valentina A. (Zootaxa, 2015)
A new species of Plecoptera, Amphinemura zwicki sp. n. from the Primorsky Region south of the Russian Far East, is described and illustrated. Relationships with its close relatives are discussed.